Ethnic origin in cancer clinical trials: overrated or understated? A comprehensive analysis of cancer clinical trials leading to FDA and EMA approvals between 2020 and 2022 - Puhr, Hannah Christina; Winkler, Eva C.; Preusser, Matthias (ESMO open, 2025)
Background - Ethnic diversity in cancer clinical trials is essential to ensure that therapeutic advances are equitable and broadly applicable in multicultural societies. Yet, missing consensus on the documentation of ethnic origin, partially based on the complexity of the terminology and fear of discrimination, leads to suboptimal patient management of minority populations. Additionally, eligibility criteria, such as stringent laboratory cut-offs, often fail to account for variations across ethnic groups, potentially excluding patients without evidence-based justification. - Patients and methods - This analysis addresses this issue by investigating ethnic diversity in clinical trials that led to European Medicines Agency (EMA) and Food and Drug Administration (FDA) approvals between 2020 and 2022. Trials were identified from FDA and EMA databases, and available protocols and full-text publications were reviewed for documentation of ethnic background and eligibility criteria for organ function (bone marrow, liver, and renal). Descriptive statistics were applied to summarize the findings. - Results - Of the 56 trials analyzed, only two-thirds of primary result publications included information on ethnic origin. Caucasian and Asian groups were documented in most of those trials and also had the highest percentages of participants across trials, while other ethnic subgroups were less frequently documented and only made up a small proportion of trial participants. Eligibility criteria often set strict organ function cut-offs that did not consider variations among ethnic groups, potentially excluding minorities. The Cockcroft-Gault formula was frequently used to assess kidney function, despite its known limitations for multiethnic cohorts. - Conclusions - Ethnic homogenous participants and eligibility criteria that favor majority groups limit the applicability of findings in diverse populations, leading to inadequate patient management. While United States guidelines encourage inclusivity, similar recommendations are lacking in Europe. Thus European regulatory authorities, research organizations, and patient advocates should establish guidelines to improve ethnic diversity in cancer clinical trials, aligning research practices with the increasingly multicultural composition of European societies.